Does Education Important For The Development Of Creative Industry Enterprises? Evidence From Jember Regency - Zainuri, Zainuri; V, Sebastiana; W, Regina Niken; Amijaya, Rachmania Nurul Fitriya; Yasin, Mohammed Zeqi (MediaTrend, 2024)
Jember Regency is one of the regional areas in East Java Province, famous for its creative industry potential. The creative industry areas in Jember Regency contribute regional income of IDR 1,000,000 – IDR 6,000,000 per capita, restricted in the tourism and creative industry sectors. They know the significant and promising potential in the creative industry. This study chose creative industry areas as research objects. The aim is to determine the growth and development of creative industries and to analyze social capital's role in supporting creative industry institutions' development in Jember Regency. Based on the results of research using a Likert scale and OLS processing, creative industry players in creative industry areas in Jember Regency, such as Arjasa District, Jelbuk District, Ledokombo District, and Balung District, have creative industries that built with their capital. Even though they still don't have legality and the workers don't have special qualifications, the profit earned from the creative industry can contribute to regional income and product turnover 5 times a month. In addition, it is also that the amount of capital and age does not affect the institutional development of creative industries in the Jember Regency. From the research results, the government's role as a supporter is still not optimal. This condition is supported by research results whose businesses have not been incorporated or have legality. Communication and cooperation between the regional creative industry apparatus and the central government are to be more stringent. Strategies for developing business capacity-building policies and access to financing, increasing the creation of start- up opportunities, and increasing the added value of social enterprises can be applied to support the development of creative industries.